Case Report: Novel Disseminated Paecilomyces formosus Infection in a Dog - Anderson, Stephanie; Barrantes Murillo, Daniel Felipe; Womble, Mandy; Gibbs, Nicole; Harrell, Karyn; Negrão Watanabe, Tatiane Terumi (Frontiers in Veterinary Science, 2022)
A 2.5-year-old, 25.5 kg, spayed female Australian Shepherd dog had a 2-month history of shifting leg lameness in all limbs, tetraparesis, progressive lethargy, and severe pain. On the physical examination, fever (40.61℃), tachycardia, tachypnea, mild diffuse pelvic limb muscular atrophy, left prescapular and right popliteal lymphadenomegaly were observed. Due to the poor prognosis and difficult pain management, humane euthanasia was elected. Macroscopic and histological findings revealed multifocal to coalescing granulomas with central areas of lytic necrosis within the right femur, left humerus, left scapula, left biceps brachii, right semimembranosus muscle, liver, spleen, and lymph nodes. The necrotic areas contained myriad intralesional, intracellular, and extracellular negatively stained, non-pigmented, septate acute angle branching hyphae with parallel walls measuring 3-6 µm in width with polar bulbous projections measuring 7-13 µm in width. Fresh samples of the liver were submitted for fungal culture. Panfungal PCR targeting the major conserved genes - ITS, TUB, CAL - confirmed Paecilomyces formosus. Paecilomyces spp. are members of anamorphic fungi classified under the phylum Ascomycota. Paecilomycosis is an uncommon fungal infection caused by Paecilomyces spp with a disease reported in humans and animals ranging from superficial to systemic clinical forms affecting both immunocompromised and immunocompetent individuals. In dogs, disseminated paecilomycosis has been reported, but the species of fungi are not always determined. To our knowledge, this is the first case of disseminated paecilomycosis caused by P. formosus infection in a dog.